PENGARUH ALIH FUNGSI KAWASAN HUTAN DAN PERTANIAN TERHADAP PEREKONOMIAN ACEH - Harry Gunawan; Nur Aidar; Cut Risya Varlitya (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2021)
AbstractThe purpose of this study was to determine the effect of the conversion of forest and agricultural areas on Aceh's economy. The variables used in this study are the variable of forest land use conversion and agricultural land use change, then its effect is analyzed on Aceh's GRDP using secondary data from 2001-2017. The model used in the study is the multiple linear regression analysis model or Ordinary Least Square (OLS) processed with Eviews 10. The results, it can be concluded that the conversion of forest land functions has a negative and significant effect on economic growth, while the area of agricultural land has a positive and significant effect on Aceh economic growth. Thus, it is suggested to the government to make effective policies related to the management of forest areas in Aceh, so that they can benefit from the conversion of forests and agriculture that can have a good impact on the economy and welfare of the peopleKeywords: Aceh GDRP, Forest Land Area, Agricultural Land Area.